Tethered pincer complexes as recyclable homogeneous catalysts - MCDONALD, AIDAN (My University, 2015)
The utilisation of recyclable pincer complexes in applied catalysis is a vital progression in the field of homogeneous catalysis. This is routed in the high thermal and mechanical stability that most pincer complexes demonstrate. The pincer framework of a tridentate bis-chelating ligand system, with two dative appendages and a direct metal ligand σ-bond, shows higher stability than most other coordination complexes. This is essential to testing immobilisation and recycling methods for homogeneous catalysis. We review herein efforts made towards the efficient immobilisation (heterogenisation) of homogeneous pincer complexes, and their application in a variety of catalytic processes. Recycling of pincer complexes, as described herein, does not display high rates of ligand and metal leaching. The outcome of this is an array of homogeneous catalyst immobilisation techniques which can be probed using pincer complexes.
PUBLISHED
Keywords: Catalysis; Catalyst recycling; Heterogenised homogeneous catalysts; Immobilised catalysts; Pincer complexes